2021
DOI: 10.1371/journal.pone.0251487
|View full text |Cite
|
Sign up to set email alerts
|

Validating controlled attenuation parameter in the assessment of hepatic steatosis in living liver donors

Abstract: Introduction Hepatic steatosis (HS) negatively impacts transplant outcomes in living liver donors. To date, liver biopsy is preferred for HS evaluation. This study aims to evaluate the measurement of controlled attenuation parameter (CAP) as a diagnostic tool of HS in living liver donors. Methods Candidates recruited to this study, conducted from April 2016 to February 2020, were potential donors who had undergone transient elastography using Fibroscan® and CAP measurements at liver segments VI and VII, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…ing 150 LLD, found an AUROC of .88 for the detection of steatosis (significant or any degree) with CAP, yielding a sensitivity of 87% and specificity of 84% at a cut off value of 276 dB/m. 22 In a retrospective study of 56 healthy potential donors, CAP detected moderate-severe steatosis with an AUROC of .88 (sensitivity 83%, specificity 82% for a cutoff value of 276 dB/m, P < .001). 24 Another study of 54 potential liver donors found even greater accuracy, demonstrating an AUROC of .96 (sensitivity 100%, specificity 89% for a cutoff value of 257 dB/m, P < .001) in detecting any degree of steatosis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…ing 150 LLD, found an AUROC of .88 for the detection of steatosis (significant or any degree) with CAP, yielding a sensitivity of 87% and specificity of 84% at a cut off value of 276 dB/m. 22 In a retrospective study of 56 healthy potential donors, CAP detected moderate-severe steatosis with an AUROC of .88 (sensitivity 83%, specificity 82% for a cutoff value of 276 dB/m, P < .001). 24 Another study of 54 potential liver donors found even greater accuracy, demonstrating an AUROC of .96 (sensitivity 100%, specificity 89% for a cutoff value of 257 dB/m, P < .001) in detecting any degree of steatosis.…”
Section: Discussionmentioning
confidence: 97%
“…There are a few similar studies from the Middle East and East Asia which have shown comparable results. The largest study, including 150 LLD, found an AUROC of .88 for the detection of steatosis (significant or any degree) with CAP, yielding a sensitivity of 87% and specificity of 84% at a cut off value of 276 dB/m 22 . In a retrospective study of 56 healthy potential donors, CAP detected moderate‐severe steatosis with an AUROC of .88 (sensitivity 83%, specificity 82% for a cutoff value of 276 dB/m, P < .001) 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increasing incidence of obesity and nonalcoholic fatty liver disease (NAFLD), the global prevalence of liver steatosis has risen among organ donors [42]. Currently, the main methods employed to evaluate hepatic steatosis include gross visual recognition, imaging analysis [43], controlled attenuation parameter (CAP) [44], and biopsies [45]. Steatotic donor livers (SDLs), defined as livers with severe steatosis (≥30% fat content), have emerged as a new source for expanding the donor pool.…”
Section: Definitionmentioning
confidence: 99%